ANALYSIS OF POVERTY IN JAVA-BALI ISLAND AND REGIONS OUTSIDE JAVA-BALI - Sri Nathasya; Tri Haryanto; Ni Made Sukartini (Faculty of Economics and Business, University of Pasundan, 2022)
The urgency of this study is to analyze poverty based on the characteristics of districts/cities in Java-Bali and regions outside Java-Bali. This study used panel data from 2010-2019 in 128 regencies/cities in the Java-Bali islands, and 382 regencies/cities outside Java-Bali region. Analysis using the STATA application with the analytical used is Fixed Effect Model (FEM). Access to electricity has a negative and significant effect on poverty while access to sanitation has a negative and insignificant effect on poverty in Java-Bali. The KUR program, access to clean water, GRDP, education and population have positive and significant impact on poverty in the Java-Bali region. The results of the analysis in areas outside Java-Bali suggest that GRDP has a positive but insignificant effect on poverty while the KUR Program, access to electricity, access to water, access to sanitation, education and population have significant and positive effect on poverty.